Segmented mechanics for traction of impacted maxillary canine: case report with a 3-year follow-up (Bioscience Journal, 2019)
Young patients are increasingly concerned with smile aesthetics, resulting in the early visit to the dental office. It is of great importance that professionals such as orthodontists, pediatric dentists, and general practitioners are aware of the potential changes in positioning and development that may compromise aesthetics, considering they may prevent future complex orthodontic treatments. This case report describes the treatment of a patient aged 9 years and 4 months, who complained at assessment about the size and position of maxillary incisors. Clinically, the patient presented atresic maxilla and eruption of teeth 12 and 22. The poor positioning of tooth 22 alerted for the potential retention of tooth 23. A two-phase treatment was proposed, including an intercepting phase and a corrective phase. In the intercepting phase, rapid maxillary expansion (RME) was performed, which increased the room for eruption of tooth 23 and prevented the collapse of tooth 22. After the activation period, the Haas expander was locked and removed six months later. Twenty-five months after the removal, the second phase started with fixed corrective orthodontics and traction of tooth 23, for which the enamel was drilled and traction was performed using the segmented technique with a 0.019" x 0.025" Titanium Molybdenum Alloy (TMA) cantilever and anchorage in passive transpalatal arch (PTA). The use of this technique minimizes the side effects on the teeth adjacent to tooth 23 and enamel drilling prevents potential losses of the traction device by detachment. After 4 months of segmented mechanics, the devices were removed and the PTA was maintained. Twenty-six months later, the patient was 14 years and 4 months old, presenting direct subdivision Class III molar relationship, upper and lower crowding, and unsatisfactory relationship between bone bases due to the excessive mandibular growth. A new RME was performed, and after 3 months a Capelozza Pattern III fixed appliance was installed in the lower arch. Additionally, an upper fixed appliance was installed after the RME retention period. One year and 4 months later, the appliances were removed and a maxillary Hawley plate was installed with a 0.6-mm fixed mandibular intercanine arch. The follow-up lasted 3 years and 4 months and the results were maintained, preserving the occlusal and facial characteristics.